Draft Annual Plan 1980-81 Administration of Union Territory of Dadra and Nagar-Haveli - Planning Commission (Planning Commission, 1980)
As per 1971 Census, the population m of this Territory is 74,170 consisting of 36,964 males an 37,206 females. The area is predominantly rural and. tribal with 86.89% of the population be in Scheduled Tribes and 1.47% Scheduled Castes.
Union Territory of Dadra and Nagar Haveli